Extrarenal Wilms tumor in children: A retrospective observational case series. Issue 5 (October 2020) - Liang, Haiyan; He, Yuzhu; Fu, Libing; Tian, Jun; Sun, Ning; Yu, Tong; Huang, Yangyue; Lin, Defu; Wang, Guannan
Summary: Introduction: Pediatric extrarenal Wilms tumor (ERWT) is rare. The diversity of clinical characteristics makes diagnosis, treatment and judging the prognosis difficult. Long-term follow-up outcomes and the possible prognostic factors of ERWT are still insufficient. Objective: To identify the characteristics, therapeutic strategies and long-term results of pediatric ERWT. Patients and methods: All children with ERWT in our institution were retrospectively reviewed. The National Wilms Tumor Study (NWTS) system was used to evaluate tumor grade. Results: Among the 876 patients with Wilms tumor in our institution between January 1986 and July 2018, 5 (0.57%) patients had ERWT. Of the 5 children with ERWT, the locations were the retroperitoneum in 3 patients (including 1 presacral) and the gubernaculum testis of an undescended testis and a duplicate sigmoid colon in 1 patient each. Two patients were stage II, and 3 patients were stage III. The three patients with larger tumor sizes had preoperative tumor rupture. In the long-term follow-up, ranging from 1.0 to 10.8 years, 3 patients had disease-free survival, and 2 patients with older age, a larger tumor size and preoperative tumor rupture had recurrence with metastasis, including 1 death. Discussion: Wilms tumor extremely rarely originates outside the kidney. The current case series represents the first report of ERWT accompanied by a duplicate sigmoid colon. ERWT can coassociate with congenital gastrointestinal and genitourinary system anomalies, such as undescended testis and duplicate sigmoid colon, which provide clues to the preoperative diagnosis of ERWT. Deep and not easily palpated locations for the ERWT and older ages were associated with diagnosis delay, which can lead to enlargement of the tumor, an increased risk of preoperative tumor rupture and advancement of the tumor stage. Although only 3% of ERWT cases were metastatic according to previous reports, 2 of 5 patients (patients 1 and 4) with older age, larger tumor size and preoperative tumor rupture had recurrence and metastases in the current study. Thus, patients with poor prognoses often require aggressive combination treatments, and more attention is needed in terms of the recurrence, metastases and fatality of ERWT. Conclusion: ERWTs are rare tumors and can coassociate with congenital gastrointestinal and genitourinary system anomalies. The prognosis of ERWT is comparable to that of Wilms tumor located at normal anatomical sites. Summary table 1 Characteristics of 5 patients with extrarenal Wilms tumor. Summary table 1 Case No. Age (y) Gender Chief complaint Location Associated malformation Maximum tumor diameter (cm) Preoperative tumor rupture Treatment Pathological type Stage Outcome Survival time (y) 1 5.0 Male Abdominal pain after accidental fall, hematochezia with paleness and fever Retroperitoneum – 20.0 Yes Preoperative chemotherapy (VCR) Mixed III Recurrence with multiple metastases and death 1.0 +Surgery +Chemotherapy (Act D + VCR + DOX) 2 3.4 Female Underbelly mass with low back pain Presacral – 8.2 Yes Preoperative chemotherapy (Act + VCR) Mixed III Disease-free survival 10.8 +Surgery +Chemotherapy (Act D + VCR + DOX) + Radiotherapy 3 3.4 Female Abdominal pain with paleness Duplicate sigmoid colon Duplicate sigmoid colon 7.0 No Surgery Blastemal II Disease-free survival 3.3 +Chemotherapy (EE-4A, Act + VCR) 4 9.8 Male Back and abdominal pain Retroperitoneum (with thrombus of inferior vena cava) – 13.3 Yes Preoperative chemotherapy (Act + VCR) Mixed III Recurrence with multiple pulmonary metastases a 1.8 +Surgery +Chemotherapy (DD-4A, Act D + VCR + DOX) + Radiotherapy 5 2.8 Male Inguinal area mass and cryptorchism Gubernaculum testis Undescended testis 1.1 No Surgery Epithelial II Disease-free survival 1.5 +Chemotherapy (EE-4A, Act + VCR) Patient order by time of visit. a Chemotherapy is ongoing for multiple pulmonary metastases.